Analysis of the relationship between stored grains and category of management of storage systems in Brazil (Research, Society and Development, 2022)
Storage systems are essential for agricultural production, especially for grain productive chains. However, it is dependent on public and private agents for its viability and maintenance as a service. The present study aims to evaluate how grain storage is being carried out in the different regions of Brazil in relation to the managing economic agents: Private Initiative, Government, Cooperative and Mixed Economy. The methodology for this study makes use of Social Network Analysis that allow investigating the relationships between stored products and the types of economic agents present in each region. The results showed that warehouses often have a wide variation in the types of grain stored and there is a predominant role of the Private Initiative in the management of these storage systems.